Changes in the TCRβ Repertoire and Tumor Immune Signature From a Cutaneous Melanoma Patient Immunized With the CSF-470 Vaccine: A Case Report - Aris, Mariana; Bravo, Alicia Inés; Pampena, María Betina; Blanco, Paula Alejandra; Carri, Ibel; Koile, Daniel; Yankilevich, Patricio; Levy, Estrella Mariel; Barrio, María Marcela; Mordoh, José (Frontiers in Immunology, 2018)
The allogeneic therapeutic vaccine CSF-470 has demonstrated a significant benefit over medium-dose IFNα2b in the distant metastasis-free survival for stages IIB-IIC-III cutaneous melanoma patients in a randomized phase II/III clinical trial (CASVAC-0401, NCT01729663). At the end of the 2-year CSF-470 immunization protocol, patient #006 developed several lung and one highly-immune infiltrated subcutaneous melanoma metastases; this later was excised. In this work, we analyzed the changes throughout vaccination of blood immune populations, with special focus on the T-cell repertoire. Immunohistochemistry revealed a marked increase in CD8+, CD4+, and CD20+ lymphocytes infiltrating the metastasis relative to the primary tumor. Lymphocytes were firmly attached to dying-tumor cells surrounded by Granzyme-B granules. Whole exon sequencing assessment indicated a moderate-to-high tumor mutational burden, with BRAFV600E as main oncogenic driver. Mutational signature presented large numbers of mutations at dipyrimidines, typical of melanoma. Relevant tumor and immune-related genes from the subcutaneous metastasis were addressed by RNA-Seq analysis, revealing expression of typical melanoma Ags and proliferative tumor-related genes. Stimulatory and inhibitory immune transcripts were detected as well as evidence of active T-cell effector function. Peripheral blood monitoring revealed an increase in CD4+ and CD8+ cells by the end of the immunization protocol. By CDR3 TCRβ sequencing, generation of new clones and an increase in oligoclonality was observed in the peripheral T-cells immune repertoire throughout immunization. A shift, with the expansion of selected pre-existing and newly arising clones and reduction of others, was detected in blood. In tumor infiltrating lymphocytes, prevalent clones (50%) were both new and pre-existing ones that were expanded in blood following CSF-470 immunization. These clones persisted in time, since 2-years after completing the immunization, 51% of the clones present in the metastasis were still detected in blood. This is the first report of the TCRβ repertoire from a melanoma patient immunized with the CSF-470 vaccine. In this patient, the changes observed in peripheral immune populations as well as in the tumor compartment after immunization suggest that the vaccine can induce an anti-tumor adaptive immune repertoire that can reach tumor lesions and persists in blood for at least 2 years.